Women's assets and intrahousehold allocation in rural Bangladesh: testing measures of bargaining power - Quisumbing, Agnes R.; de la Briere, Benedicte (International Food Policy Research Institute, 2000)
This paper examines how differences in the bargaining power of husband and wife affect the distribution of consumption expenditures in rural Bangladeshi households. Two alternative measures of assets are used: current assets and the value of assets brought to marriage. Results show that both assets at marriage and current assets are strongly determined by the human capital of husband and wife and the characteristics of their origin families. For both husband and wife, parents’ landholdings are a consistent determinant of both assets at marriage and current assets. Contrary to the unitary model, husband’s and wife’s assets have different effects on the allocation of expenditures within the household. Wife’s assets have a positive and significant effect on the share of expenditures on children’s clothing and education. This result is robust to the choice of asset measure and estimation procedure. After endogeneity of assets is accounted for, husband’s current assets have a positive and significant effect on the food expenditure share. Neglecting the endogeneity of asset measures to individual and parental characteristics may lead to biased estimates of the impact of men’s and women’s assets on expenditure shares.